Cystic adventitial of the popliteal artery Clinical case report - كنجو, حسام (Latakia University Journal -Medical Sciences Series, 2022)
This is a 38-year-old athlete, without vascular risk factors, with intermittent claudication of the right leg, pain in the calf, and kept femoral pulse. The radiological examination included an arterial Doppler ultrasound, CT angiography of the lower extremities and arteriography. The diagnosis was a adventitial cyst popliteal artery. The treatment consisted of resection of the popliteal artery at headquarters cystic area and its replacement by a reversed saphenous internal vein graft. The suites were simple. The followed for 12 months postoperatively was satisfactory, with graft patency 100%. Keywords: Cyst adventitial, Popliteal artery, intermittent claudication.